Kaidah Fiqihiyyah Ekonomi Islam Mengetahui Kaidah-Kaidah Fiqih dalam Ekonomi Islam - Septian Fiktor Riyantoro; Misbachul Anam (CV. ULIL ALBAB CORP, 2024)
Islamic fiqh always discusses the topics of economics and economic concepts. To help Muslims in discussing a theme of the economic law of Islam, it is necessary to learn the rules of fiqh to gain ease in knowing the laws of the contemporary economy that has no sharih nash (certain reference) in the Qur’an and hadith. In addition, the rules of fiqh also help us to master the branch problems (furu’iyah) that are more various and incalculable, in only a short time an easy way, which is through a solid and succinct expression in the form of rules of fiqh, either fiqh rules related to contract (transaction), mal (property assets), banking, and arbitration